Neonatal testis growth recreated in vitro by two‐dimensional organ spreading. Issue 12 (29th September 2018) - Kojima, Kazuaki; Nakamura, Hiroko; Komeya, Mitsuru; Yamanaka, Hiroyuki; Makino, Yoshinori; Okada, Yuki; Akiyama, Haruhiko; Torikai, Nobuhito; Sato, Takuya; Fujii, Teruo; Kimura, Hiroshi; Ogawa, Takehiko
Abstract: Organ culture experiments can be hampered by central degeneration or necrosis due to the inadequate permeation of oxygen and nutrients, which deteriorates the function and growth of cultured tissues. In the current study, we aimed to overcome this limitation of organ culture through spreading the tissue two dimensionally on an agarose gel stand and molding into a disc shape by placing a ceiling of polydimethylsiloxane (PDMS) chip, which is highly oxygen permeable. By this, every part of the tissue can receive a sufficient supply of oxygen through PDMS as well as nutrients through the agarose gel below. This method not only prevented central necrosis of tissues, but also supported the tissue growth over time. In addition, such growth, as volume enlargement, could be easily measured. Under these conditions, we examined the effect of several factors on the growth of neonatal mouse testis, and found that follicle stimulating hormone (FSH) and insulin significantly promoted the growth. These results are in good agreement with previous in vivo reports. Notably, the growth achieved over 7 days in our in vitro system is almost comparable to, about 80% of, that observed in vivo. Thus, we successfully monitored the promotion of tissue growth beyond the limits of the conventional organ culture method. This extremely simple method could offer a unique platform to evaluate the growth as well as functional properties of organs, not only the testis but also others as well. Abstract : Tissues and organs under regular three‐dimensional culture condition face a limit of their growth and are never able to enlarge as a sphere beyond around 1 mm in diameter. The authors devised a new method named PDMS‐ceiling, by which neonatal mouse testis tissues were spread on the surface of agarose gel and allowed growing 2‐dimensionally. The growth rate was nearly comparable to that as in vivo, which was well beyond the limit of conventional culture method.